Effectiveness of Audio-Visual-Based Health Education in Improving Adolescents Knowledge of HIV/AIDS - Wahyuni Maria Prasetyo Hutomo; Irfandi Rahman; Josepha Maria Tamaela; Susan Kamese; Irma Idris (Indonesian Journal of Global Health Research, 2026)
Globally, the number of HIV/AIDS cases remains high, while in Indonesia the disease continues to be a serious public health problem. This situation is particularly evident in Sorong City, West Papua Province, which continues to record a relatively high number of cases. Given these conditions, researchers are interested in studying the impact of audio-visual health education on adolescents' knowledge of HIV/AIDS as an effort to support the prevention of infectious diseases among the younger generation. This Study aimed to determine the effect of audio-visual-based health education on adolescents knowledge of HIV/AIDS at SMK Negeri 5 Sorong City. This pre-experimental design with one group pretest-posttest. The sampel comprised 54 students selected with total sampling teqnique. Data were collected using an HIV/AIDS knowledge questionnaire administered before and after an audio-visual based health education intervention. Data were analyzed using the Wilcoxon signed rank test. This study showed that before intervention adolescents level knowledge varied, with the majority categorized as having poor knowledge (51,9%). After the audio visual health education was conducted good knowledge increased to 88,9%. Analysis using the Wilcoxon signed-rank test p-value of 0.00 (<0.05) indicating a significant effect of the intervention. The study concluded that audio-visual-based health education significantly improved adolescents’ knowledge about HIV/AIDS at SMK Negeri 5 Sorong City.